LEGAL FRAMEWORK OF THE PUBLIC FINANCIAL CONTROL OF THE ACTIVITIES OF LOCAL SELF-GOVERNMENT BODIES ON THE IMPLEMENTATION OF ENVIRONMENTAL POLICY - Yefimov , Yuriy (Theory and Practice of Public Administration, 2020)
Effective implementation of public environmental policy at the local level is impossible without public financial control of the activities of local self-government bodies, which are one of the main stakeholders in this field. In our opinion, one of the main issues to be discussed in the Ukrainian professional environment regarding the nature of the organization of public financial control at the local level is the definition of the criteria for the distinction between “local finances” and “finances of local governments”, since in most democratic countries there is no opposition between local state administrations and local governments, respectively, between their separate financial systems. The basic principles of public administration presuppose the existence of a single vertical of authority from the central government and regional authorities to the local institutions of government.The Lima Declaration of Guidelines on Auditing Precepts, adopted by the IX INTOSAI Congress in October 1977, defines (Section 1) public audit as an integral part of the public financial administration. The latter is considered in this international normative document as the sphere of management of public funds. That is, in Western practice and professional literature, the concept of “local finances” is considered solely as a financial system of unified and legally independent territorially organized public authorities. Whereas in the relevant domestic legal acts since the mid-1990s there is an overpowering dualism in basic approaches to solving this problem.Therefore, the purpose of the article is to investigate the formation of the legal framework of public financial control of the activities of local self-government bodies in the implementation of environmental policy in terms of the distinction between “local finance” and “local government finances” in the context of modern European-oriented transformation of public administration.According to the results of the study, it is concluded that a sufficient legal and regulatory framework has been formed to allow the public financial control of activities of local self-government bodies in the implementation of environmental policy in the context of a modern European-oriented transformation of public administration. At the same time, the interaction of local governments and other local stakeholders in the implementation of environmental policy remains ineffective. Identifying opportunities for improving such engagement should be a further area of ​​research in this field.